Advertising campaign performance evaluation indicators: essential analysis - Larysa Harmider; Andrii Kutsynskyi; Mariia Kutsynska (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2022)
The current state of the research of the theoretical basis for evaluating the effectiveness of the advertising campaign, presented in the special and scientific literature, is analyzed, the results of which indicate that attention is paid to these issues and problems. At the same time, with regard to the theoretical aspects of evaluating the effectiveness of an advertising campaign taking into account various factors and influencing factors, it is appropriate to note that such issues are described quite concisely in the recommendations of marketing practitioners or are summarized in scientific works, which, in turn, emphasizes the importance of creating such scientific basis for application in the practical activity of economic entities of various forms of ownership under modern conditions of functioning of the Ukrainian market. The indicators proposed for use by practitioners to evaluate the effectiveness of the advertising campaign were analyzed, and they were divided into two groups: marketing and financial. Marketing indicators for evaluating the effectiveness of an advertising campaign include: CTR (clickability rate); CR (conversion rate); CPC (cost per click); CPM (cost per thousand impressions); CPA (cost per action); CPI (cost per mobile app install). Financial indicators for evaluating the effectiveness of an advertising campaign include: ROAS (return on investment in advertising); ROI (return on investment ratio); ROMI (marketing return on investment ratio); CAC (cost of attracting a new customer); LTV (profit during the period of cooperation with the client). The essence and functional purpose of marketing and financial indicators for evaluating the effectiveness of the advertising campaign are analyzed.